2018
DOI: 10.1101/508127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of tumour initiation, spatial and temporal progression under multiple lines of treatment

Abstract: Driver mutations alter cells from normal to cancer through several evolutionary epochs: premalignancy, early malignancy, subclonal diversification, metastasis and resistance to therapy. Later stages of disease can be explored through analyzing multiple samples collected longitudinally, on or between successive treatments, and finally at time of autopsy. It is also possible to study earlier stages of cancer development through probabilistic reconstruction of developmental trajectories based on mutational inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 56 publications
3
69
0
Order By: Relevance
“…The data for this study consisted of multiple samples collected from each patient (pre-and post-treatment) as well as autopsy samples. Phylogenetic analysis, subclonal reconstruction and tree building was done with the PhylogicNDT package 36 .…”
Section: Phylogenetic Analysis Of Multiple Samples From the Same Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for this study consisted of multiple samples collected from each patient (pre-and post-treatment) as well as autopsy samples. Phylogenetic analysis, subclonal reconstruction and tree building was done with the PhylogicNDT package 36 .…”
Section: Phylogenetic Analysis Of Multiple Samples From the Same Patientmentioning
confidence: 99%
“…We analyzed WES data from pre-treatment and post-progression cfDNA, post-progression biopsy, and 17 autopsy specimens (Figs. 3b-d; Supplementary Table 5), and studied the clones and their phylogenetic structure with PhylogicNDT 36 . Interestingly, FGFR2 V564L…”
Section: Introductionmentioning
confidence: 99%
“…having CCFs of ≥ 10% at one or more timepoints) to derive likely phylogenies for each patient (Methods, Supplementary Table 10, Extended Data Figures 5–7). Using PhylogicNDT 18 , we identified subclones by n -dimensional clustering of CCFs of individual events across samples, estimated their phylogenetic relationships and modelled the growth dynamics of each subclone (Methods). We focused on the 5 patients with WES from 4 or more pre-treatment time points (Patients 1, 4, 5, 18, and 19).…”
Section: Resultsmentioning
confidence: 99%
“…We focused this analysis on the 35 subclones detected in 16 patients whose leukaemias displayed overall non-logistic WBC expansion (since those with overall LOG growth lacked abundant drivers). We inferred the distribution of growth rates of individual subclones and the differences to their parents using an MCMC algorithm that samples an ensemble of likely phylogenetic trees for each patient ( PhylogicNDT GrowthKinetics 18 ; Methods). The model also takes into account the reads supporting each somatic mutation, tumour purity, absolute copy-number, and the WBC measurements (Extended Data Figure 5d).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that the analysis of serial samples from the same patient can greatly increase the sensitivity and confidence in the detection of subclonal mutations. 1,27 CLL heterogeneity is not restricted to somatic mutations. Epigenetic mechanisms, such as DNA methylation, chromatin remodeling, and posttranslational histone modification, also contribute to tumor diversity and play a role in cancer evolution.…”
Section: Tumor Heterogeneity In Cllmentioning
confidence: 99%